ClCRY2 facilitates floral transition in Chrysanthemum lavandulifolium by affecting the transcription of circadian clock-related genes under short-day photoperiods. Issue 1 (1st November 2018) - Yang, Li-wen; Wen, Xiao-hui; Fu, Jian-xin; Dai, Si-lan
Abstract: Plants sense photoperiod signals to confirm the optimal flowering time. Previous studies have shown that Cryptochrome2 ( CRY2 ) functions to promote floral transition in the long-day plant (LDP) Arabidopsis ; however, the function and molecular mechanism by which CRY2 regulates floral transition in short-day plants (SDPs) is still unclear. In this study, we identified a CRY2 homologous gene, ClCRY2, from Chrysanthemum lavandulifolium, a typical SDP. The morphological changes in the C. lavandulifolium shoot apex and ClFTs expression analysis under SD conditions showed that adult C. lavandulifolium completed the developmental transition from vegetative growth to reproductive growth after eight SDs. Meanwhile, ClCRY2 mRNA exhibited an increasing trend from 0 to 8 d of SD treatment. ClCRY2 overexpression in wild-type (WT) Arabidopsis and C. lavandulifolium resulted in early flowering. The transcript levels of the CONSTANS-like ( COL ) genes ClCOL1, ClCOL4, and ClCOL5, and FLOWERING LOCUS T ( FT ) homologous gene ClFT1 were upregulated in ClCRY2 overexpression ( ClCRY2- OE) C. lavandulifolium under SD conditions. The transcript levels of some circadian clock-related genes, including PSEUDO-REPONSE REGULATOR 5 ( PRR5 ), ZEITLUPE ( ZTL ), FLAVIN-BINDING KELCH REPEAT F-BOX 1 ( FKF1 ), and GIGANTEA ( GI-1 and GI-2 ), were upregulated in ClCRY2- OE C. lavandulifolium, while the expression levels of other circadian clock-related genes, such as EARLY FLOWERING 3 ( ELF3 ), ELF4, LATE ELONGATED HYPOCOTYL ( LHY ), PRR73, and REVEILLE8 ( RVE8 ), were downregulated in ClCRY2- OE C. lavandulifolium under SD conditions. Taken together, the results suggest that ClCRY2 promotes floral transition by fine-tuning the expression of circadian clock-related gene, ClCOL s and ClFT1 in C. lavandulifolium under SD conditions. Genetics: Harnessing flower power in chrysanthemums: Researchers have identified the genes that control the timing of flowering in chrysanthemums. For most plants, day-length indicates that it is time to flower. Greenhouse growers can produce out-of-season flowers by manipulating day length, but the process is expensive. Breeding varieties that respond more quickly could reduce costs, but requires a better understanding of the underlying genetics, especially in the subset of plants triggered by short days. Si-lan Dai and co-workers at Beijing Forestry University in China investigated which genes trigger flowering in Chrysanthemum lavandulifolium, a typical short-day plant. They found that flowering of chrysanthemum is controlled by a gene previously identified in long-day plants, and that amplifying the gene produced plants that flowered much sooner than ordinary plants. These findings may help in breeding varieties that are easily induced to bloom.